2007
DOI: 10.1093/ajcn/85.4.1083
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Global Nutritional Assessment for children

Abstract: SGNA is a valid tool for assessing nutritional status in children and identifying those at higher risk of nutrition-associated complications and prolonged hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
242
8
54

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(315 citation statements)
references
References 32 publications
11
242
8
54
Order By: Relevance
“…This incidence was >50% in four of the included studies, 12,13,23,26 and the lowest rate was found in the largest cohort study which reported an incidence of 14.5%. 21 A formula using height and/or weight parameters was most commonly used to assess nutritional status.…”
Section: Methods Of Nutritional Assessmentmentioning
confidence: 77%
See 4 more Smart Citations
“…This incidence was >50% in four of the included studies, 12,13,23,26 and the lowest rate was found in the largest cohort study which reported an incidence of 14.5%. 21 A formula using height and/or weight parameters was most commonly used to assess nutritional status.…”
Section: Methods Of Nutritional Assessmentmentioning
confidence: 77%
“…Three papers excluded neonates: Rojratsirikul et al excluded infants aged less than two months, 27 whilst Secker and Jeejeebhoy and Stey et al excluded neonates aged <31 days and <28 days, respectively. 12,21 The remaining 10 studies were performed in children with a minimum age of three days and overall median age of 10.6 months. 23 Four studies were undertaken in cardiac surgical populations, 13,20,21,29 and four studies were undertaken in general surgical populations, mainly gastrointestinal/abdominal surgery.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations